Inovasi Pemasaran Produk Olahan Pangan Pesisir dalam mencapai Keunggulan Kompetitif pada Krupuk Ikan Jenggelek - Erma Yuni Kristianita; Riza Amelia Hermawati; Devi Ariska Putri; Fifin Liawati; Cucu Hayati (PUTRA JAWA PUBLISHER, 2023)
Jenggelek Fish Crackers is a typical cracker produced in East Java Province, one of its locations in the coastal village of Besuki – Situbondo with a blend of savory and crunchy flavors. We deliberately pack the jenggelek fish crackers in raw form with various sizes, so that later it will last longer and be easier to ship. The purpose of this Student Creativity Program (PKM) is to increase knowledge and skills as well as the productivity of processed fishery products. The output target in this activity is marketing innovation in the form of producing Jenggelek Fish crackers with various flavors, making attractive Jenggelek Fish product packaging, creating a digital-based marketing strategy to expand market share. The results of the activities that have been implemented include product innovation in the form of flavor variants namely Seblak, sambal matah, seaweed, Blackpaper, spicy and super spicy, packaging with a more modern design with the label “Mileneal Fish Crackers”, as well as a digital marketing strategy through social media. Media such as Whatsapp and Instagram groups. From PKM activities during these 3 months, business actors were able to reap a net profit of 65.07%.